Novel C3B/SiC2 Heterobilayer: Electro‐Optical Properties Induced by Different Interlayer Coupling. Issue 12 (29th October 2021) - Shu, Huabing
Abstract: Performing first‐principles calculations, electronic and optical properties of the C3 B/SiC2 heterobilayers with two stacked configurations are explored systematically. They are verified to be energetically and dynamically stable by their binding energies and phonon dispersions. Also, they possess moderate bandgaps and intrinsic type‐II band alignment promoting the effective separation of photogenerated electron‐hole pairs. The quasi‐particle band structure and light absorbance of the C3 B/SiC2 can be tuned significantly under different interlayer coupling induced by the stacking modes. They both exhibit strong optical absorbance coefficients (larger than 10 5 cm –1 ) in the energy range of near‐infrared to near‐ultraviolet light. More interestingly, the observed binding energies of excitons are as large as ≈800 meV in the C3 B/SiC2, which can slow the rapid recombination of photogenerated electron‐hole pairs, thus increasing the efficiency of solar energy conversion. A power conversion efficiency of ≈18.9% can be achieved in the C3 B/SiC2 . These results indicate that the C3 B/SiC2 heterobilayer has potential applications in the optoelectronic devices. Abstract : The C3 B/SiC2 heterobilayer with type‐II band alignment is predicted to possess a desirable bandgap and excellent absorbance coefficient for the sunlight, inducing high power conversion efficiency. Also, these properties can be changed by the interlayer coupling. Computational results indicate that the C3 B/SiC2 heterobilayer has highly potential applications in optoelectronic devices.